Rubberised bitumen manufacturing assisted by rheological measurements. Issue 2 (2nd April 2016) - Subhy, Ayad; Lo Presti, Davide; Airey, Gordon
Abstract : This paper investigates the effect of processing temperature and time on the rheological properties of recycled tyre rubber-modified bitumens (RTR-MBs) produced using two different base binders and an ambient ground crumb rubber modifier (CRM). The production of the RTR-MBs was accomplished by means of a standard Brookfield rotational viscometer together with a modified impeller, dual helical impeller, to allow mixing as well as real-time viscosity measurements of the produced RTR-MBs. The rheological properties of the final RTR-MBs were determined by means of standard dynamic mechanical analysis oscillatory and multiple stress creep recovery testing using a dynamic shear rheometer. The results indicate that the low processing conditions (160°C and 60 min) are not appropriate for developing RTR-MBs with enhanced physical and rheological properties. However, allowing the crumb rubber to interact with the base binder for longer mixing times (140 min) led to the development of an enhanced rubber (polymer) network structure within the blend (i.e. swelling of the CRM particles) and superior rheological properties. At the other extreme, using high-processing conditions (200°C and 140 min) led to RTR-MBs in which the rubber network had been subjected to devulcanisation and depolymerisation with a subsequent reduction in modification.